Antioxidant and hyaluronidase inhibitory activities of diverse phenolics in Phyllanthus emblica - Min Xu; Hong-Tao Zhu; Rong-Rong Cheng; Dong Wang; Chong-Ren Yang; Takashi Tanaka; Isao Kouno; Ying-Jun Zhang (Natural Product Research, 2016)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

DBOP specifies palea development by suppressing the expansion of the margin of palea in rice - Dong-Dong Zeng; Ran Qin; Md. Alamin; Rong Liang; Cheng-Cong Yang; Xiao-Li Jin; Chun-Hai Shi (Genes & Genomics, 2016)

Elliptic Shape Prior Dynamic Programming for Accurate Vessel Segmentation in MRI Sequences with Automated Optimal Parameter Selection - Da-Chuan Cheng; Sin-Kuo Chai; Shi-Rong Xu; Shing-Hong Liu (Journal of Medical and Biological Engineering, 2016)

Experimental Study of Coal and Gas Outbursts Related to Gas-Enriched Areas - Qingyi Tu; Yuanping Cheng; Pinkun Guo; Jingyu Jiang; Liang Wang; Rong Zhang (Rock Mechanics and Rock Engineering, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

A bioeroding foraminifer, Hyrrokkin sarcophaga, on deepwater corals from the South China Sea - Yu-Rong Cheng; Chang-Feng Dai (Coral Reefs, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

High-level expression of a novel recombinant human plasminogen activator (rhPA) in the milk of transgenic rabbits and its thrombolytic bioactivity in vitro - Shaozheng Song; Xin Ge; Yaobin Cheng; Rui Lu; Ting Zhang; Baoli Yu; Xueqiao Ji; Zhengqiang Qi; Yao Rong; Yuguo Yuan; Yong Cheng (Molecular Biology Reports, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Botanical Drug Puerarin Attenuates 6-Hydroxydopamine (6-OHDA)-Induced Neurotoxicity via Upregulating Mitochondrial Enzyme Arginase-2 - Jia Zhao; Yuanyuan Cheng; Chuanbin Yang; Sam Lau; Lixing Lao; Bo Shuai; Jing Cai; Jianhui Rong (Molecular Neurobiology, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Evaluation of a water-soluble adjuvant for the development of monoclonal antibodies against small-molecule compounds - Rui Liu; Ying Liu; Mei-jing Lan; Niusha Taheri; Jing-li Cheng; Yi-rong Guo; Guo-nian Zhu (Journal of Zhejiang University-SCIENCE B, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Element distribution over the surface of fish scales and its connection to the geochemical environment of habitats: a potential biogeochemical tag - TsingHai Wang; Yan-Chen Lai; Chia-Che Chiang; Yu-Rong Cheng; Yi-Kong Hsieh; Chu-Fang Wang (Environmental Monitoring and Assessment, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The effect of different genome and cytoplasm on meiotic pairing in maize newly synthetic polyploids - Mingjun Cheng; Mingmin Zheng; Shipeng Yang; Yang Li; Xingchun Dong; Jing Li; Rulong Sun; Huaxiong Li; Shufeng Zhou; Yuanqi Wu; Tingzhao Rong; Qilin Tang (Euphytica, 2016)
Allopolyploidization plays the special role in the evolution of many crops. Moreover, the evolution in early stage of some allopolyploidization events is predicted to be effected by nuclear-cytoplasmic interactions. Maize and teosintes are well model system for study of genetic recombination in allopolyploidization. In order to investigate the effects of genome organization and cytoplasm on genome evolution in newly synthesized allopolyploids (neoallopolyploids), a series of neoallopolyploids were produced by reciprocal crosses of maize and Zea perennis . By using dual-color genomic in situ hybridization, intra- and intergenomic meiosis pairing of these polyploids were quantified and compared with regard to its genome organization and cytoplasm background. In the four neoallopolyploids, the stability of maize genome is consistently lower than that of Z. perennis genome. Additional, the stability of maize genome is affected by genome ploidy. The cytoplasm, genome composition and their interaction do have the special role in chromosome paring and the meiosis behaviors in Zea allopolyploids vary significantly and showed non-diploidization. Z. perennis cytoplasm may give a relatively relaxed environment for maize genome.

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)